2019
DOI: 10.1002/er.4961
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of electrochemical charge storage capability of ZnO/CuO/reduced graphene oxide nanocomposites

Abstract: Summary Nanocomposites of ZnO/CuO with rGO were synthesized using sonochemical and thermal treatment methods. The formation of ZnO and CuO phases on the rGO sheets and both ZnO/CuO in the ternary component nanocomposites were confirmed from IR spectroscopy and X‐ray photoelectron spectroscopy. The microstructure of the nanocomposites as revealed by TEM and FE‐SEM suggested that CuO was decorated as nano‐rods, whereas ZnO particles retained the spherical shape. In case of ternary nanocomposite, both nano‐rods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, Co‐MOFs as active materials illustrate a pair of obvious oxidation and reduction peaks. This means that Co‐MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 33‐35 . Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Co‐MOFs as active materials illustrate a pair of obvious oxidation and reduction peaks. This means that Co‐MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 33‐35 . Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities.…”
Section: Resultsmentioning
confidence: 88%
“…This means that Co-MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 . [33][34][35] Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities. But the speed of capacity decay is very fast.…”
Section: Electrochemical Mechanism Analysis Of the Electrochemical mentioning
confidence: 99%
“…The FT-IR spectra of all 550 °C calcinated samples such as ZnO, NiO, CuO, ZnO–NiO, NiO–CuO, ZnO–CuO, and ZnO–NiO–CuO MMOs have been shown in Figures a and b. The strong peak around 400–550 cm –1 confirms the presence of metal–oxygen (M–O) bonds in each of the single-metal-oxide samples (ZnO, NiO, and CuO). , It is observed that the presence of the O–H group of water molecules is attributed by the broad peaks at 3424 and 3455 cm –1 for all samples . The band located near 1137 cm –1 can be attributed to the M-O-M stretching modes of ZnO, NiO, and CuO, respectively .…”
Section: Resultsmentioning
confidence: 89%
“…Developing a new mixed-metal-oxides (MMO) material by combining them into one could open up a new direction for research and applications. As an example, ZnO–NiO, NiO–CuO, and CuO–ZnO combined binary MMOs have already been used, synthesized, and tested for supercapacitor applications, and they have shown greater functional performance, compared to the independent oxides. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ion transferred number and the ion diffusion coefficient of the Al 2 O 3 -ZnO nanorod are 6.3 and 7.6 × 10 −13 cm 2 s −1 . Studies have shown that the electrochemical properties can be further improved by synthesizing the ZnO-based multicomponent electrodes [ 65 , 148 , 149 , 150 ]. Obodo et al [ 151 ] synthesized Co 3 O 4 -CuO-ZnO@GO nanocomposite films by the hydrothermal method and then examined the effect of carbon ion irradiation on the properties of the prepared nanocomposite.…”
Section: Tmos-based Electrode Materialsmentioning
confidence: 99%